A photovoltaic textile design with a stainless steel mesh fabric. (June 2022) - Borazan, İsmail; Bedeloglu, Ayse C; Demir, Ali
Solar energy is one of the most popular energy sources among the other renewable energies. Photovoltaic technology is a clean way to generate electricity from sunlight. Flexible photovoltaics enable portable electronic devices to power at off-grid conditions. Stainless steel mesh fabric was used as a substrate and electrode allowing the light to reach the photoactive layer. The photoactive layer and hole transport layer were deposited by the means of dip-coating like in the textile industry. The metal back electrode was evaporated in a thermal evaporator under vacuum. Promising results were obtained from photovoltaic measurements. About 0.69% power conversion efficiency was obtained from textile-based solar cells in this study. The textile-based metal fabric enables a flexible photovoltaic structure that can be integrated on non-planar surfaces to generate electricity, and also mesh structure allows the light to reach the photoactive layer.